Development of nanosized glucan particles with immunostimulatory function as a delivery syistem for curcumin - Colaço, Mariana Raquel Antunes (2018)
Dissertação de Mestrado em Biotecnologia Farmacêutica apresentada à Faculdade de Farmácia